Applications of Data Processing Management Data Base Book Publishing Using Microsoft Visual Basic 6.0 - Hari Utomo (Jurnal Sistem Informasi, 2003)
With the development and advancement of increasingly sophisticated information technology in this era, a very important role inside the computer, let alone a computer equipped with infrastructure is highly developed at this time make the users get the ease in processing data. A good database processing can facilitate someone to manage the data. Both the input data, search data to retrieve the data returned in the form of reports.